Study on the corrosion resistance of composite modified anti-corrosion mortar under the action of bio-organic water - Wei, Jun; Wang, Zhenshan; Xu, Jibin; Jia, Haiqin (Frontiers in Earth Science, 2023)
Abstract: The concrete structure will be seriously eroded in a sewage environment, causing substantial economic losses. Therefore, it is of great significance to repair the existing corrosion structure. This paper proposes a new type of composite high-durability mortar. With low engineering cost, it protects the main structure from corrosion while restoring the mechanical properties. Therefore, it has good engineering application value. For the new material, this test set up a total of five groups of mixing ratios. This test analyzed the water absorption, mass loss rate, compressive strength and other performance indicators of the test block in the corrosive environment, and scanned and studied the microstructure of each mortar test block after corrosion. It was found that the new anti-corrosion mortar has relatively less crystallization, dense internal structure, and significantly lighter erosion. From the mechanical properties, the strength of ordinary polymer mortar decreased by nearly 10% after erosion, while the strength of high-durability mortar increased by almost 20%. It shows that highly durable mortar has good erosion resistance. Comprehensive view, inorganic aluminum salt waterproofing agent is the most effective; priority use is recommended.